A SEMANTIC TRACI NG on GENDER issues* - Gispert-sauch, Ana (2012)
The author tries to analyze the characteristics of the genre “essay” on genderissues, from the different conceptions of the terms woman, male, man, gender,femininity, etc., to finally present some findings from 7 works of Peruvian authorsbetween the 1970s and 2000.